Networked Digital Technologies, Part I Second International Conference, NDT 2010, Prague, Czech Republic - Zavoral, Filip; Yaghob, Jakub; Pichappan, Pit.; El-Qawasmeh, Eyas.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
On behalf of the NDT 2010 conference, the Program Committee and Charles University in Prague, Czech Republic, we welcome you to the proceedings of the Second International Conference on ‘Networked Digital Technologies’ (NDT 2010). The NDT 2010 conference explored new advances in digital and Web technology applications. It brought together researchers from various areas of computer and information sciences who addressed both theoretical and applied aspects of Web technology and Internet applications. We hope that the discussions and exchange of ideas that took place will contribute to advancements in the technology in the near future. The conference received 216 papers, out of which 85 were accepted, resulting in an acceptance rate of 39%. These accepted papers are authored by researchers from 34 countries covering many significant areas of Web applications. Each paper was evaluated by a minimum of two reviewers. Finally, we believe that the proceedings document the best research in the studied areas. We express our thanks to the Charles University in Prague, Springer, the authors and the organizers of the conference.
Information and Data Management -- A New Approach for Fingerprint Matching Using Logic Synthesis -- Extracting Fuzzy Rules to Classify Motor Imagery Based on a Neural Network with Weighted Fuzzy Membership Functions -- Distributed Data-Mining in the LISp-Miner System Using Techila Grid -- Non-negative Matrix Factorization on GPU -- Chatbot Enhanced Algorithms: A Case Study on Implementation in Bahasa Malaysia Human Language -- Handwritten Digits Recognition Based on Swarm Optimization Methods -- A Framework of Dashboard System for Higher Education Using Graph-Based Visualization Technique -- An Efficient Indexing and Compressing Scheme for XML Query Processing -- Development of a New Compression Scheme -- Compression of Layered Documents -- Classifier Hypothesis Generation Using Visual Analysis Methods -- Exploiting Punctuations along with Sliding Windows to Optimize STREAM Data Manager -- A Framework for In-House Prediction Markets -- Road Region Extraction Based on Motion Information and Seeded Region Growing for Foreground Detection -- Process Mining Approach to Promote Business Intelligence in Iranian Detectives’ Police -- Copyright Protection of Relational Database Systems -- Resolving Semantic Interoperability Challenges in XML Schema Matching -- Some Results in Bipolar-Valued Fuzzy BCK/BCI-Algebras -- Security -- The Effect of Attentiveness on Information Security -- A Secured Mobile Payment Model for Developing Markets -- Security Mapping to Enhance Matching Fine-Grained Security Policies -- Implementation and Evaluation of Fast Parallel Packet Filters on a Cell Processor -- On the Algebraic Expression of the AES S-Box Like S-Boxes -- Student’s Polls for Teaching Quality Evaluation as an Electronic Voting System -- An Improved Estimation of the RSA Quantum Breaking Success Rate -- Mining Bluetooth Attacks in Smart Phones -- Users’ Acceptance of Secure Biometrics Authentication System: Reliability and Validate of an Extended UTAUT Model -- Two Dimensional Labelled Security Model with Partially Trusted Subjects and Its Enforcement Using SELinux DTE Mechanism -- A Roaming-Based Anonymous Authentication Scheme in Multi-domains Vehicular Networks -- Human Authentication Using FingerIris Algorithm Based on Statistical Approach -- Aerial Threat Perception Architecture Using Data Mining -- Payload Encoding for Secure Extraction Process in Multiple Frequency Domain Steganography -- An Implementation of Digital Image Watermarking Based on Particle Swarm Optimization -- Genetic Cryptanalysis -- Multiple Layer Reversible Images Watermarking Using Enhancement of Difference Expansion Techniques -- Modeling and Analysis of Reconfigurable Systems Using Flexible Nets -- Using Privilege Chain for Access Control and Trustiness of Resources in Cloud Computing -- Social Networks -- Modeling of Trust to Provide Users Assisted Secure Actions in Online Communities -- A Collaborative Social Decision Model for Digital Content Credibility Improvement -- Improving Similarity-Based Methods for Information Propagation on Social Networks -- Approaches to Privacy Protection in Location-Based Services -- Social Media as Means for Company Communication and Service Design -- A Problem-Centered Collaborative Tutoring System for Teachers Lifelong Learning: Knowledge Sharing to Solve Practical Professional Problems -- Bridging the Gap between Web 2.0 Technologies and Social Computing Principles -- Ontology -- Using Similarity Values for Ontology Matching in the Grid -- Rapid Creation and Deployment of Communities of Interest Using the CMap Ontology Editor and the KAoS Policy Services Framework -- Incorporating Semantics into an Intelligent Clothes Search System Using Ontology -- SPPODL: Semantic Peer Profile Based on Ontology and Description Logic -- Ontology Based Tracking and Propagation of Provenance Metadata -- Real Time Biometric Solutions for Networked Society -- A Real-Time In-Air Signature Biometric Technique Using a Mobile Device Embedding an Accelerometer -- On-Demand Biometric Authentication of Computer Users Using Brain Waves -- Encrypting Fingerprint Minutiae Templates by Random Quantization -- Web Applications -- Method for Countering Social Bookmarking Pollution Using User Similarities -- A Human Readable Platform Independent Domain Specific Language for WSDL -- A Human Readable Platform Independent Domain Specific Language for BPEL -- Impact of the Multimedia Traffic Sources in a Network Node Using FIFO scheduler -- Assessing the LCC Websites Quality -- Expediency Heuristic in University Conference Webpage.
Keywords: Library science; Computer communication systems; Application software; Artificial intelligence; Information storage and retrieval; Software engineering; Library Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence; Information Storage and Retrieval; Software Engineering